Proceedings of the 9th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design: Dri 2017
DOI: 10.17077/drivingassessment.1613
|View full text |Cite
|
Sign up to set email alerts
|

Time to Arrival Estimates, (Pedestrian) Gap Acceptance and the Size Arrival Effect

Abstract: Summary:Various studies have found that road users' acceptance of gaps to cross in front of another vehicle is dependent on the approaching vehicle's size, with smaller accepted gaps in front of smaller vehicles. At the same time, the so called size arrival effect is well known from research on time to collision / time to arrival estimates, where larger objects / vehicles tend to be judged as arriving earlier than smaller objects / vehicles. However, so far there has been no attempt to connect these two approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…For example, it has been shown that opponents in sports were subconsciously perceived as more aggressive when being dressed in black than in white (Frank & Gilovich, 1988; Webster et al., 2012). Past studies demonstrated that traffic participants chose larger gaps when the approaching vehicle appeared to be more threatening, although these studies investigated the effect of car size, not brightness (Horswill et al., 2005; Mathieu et al., 2017; Petzoldt et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that opponents in sports were subconsciously perceived as more aggressive when being dressed in black than in white (Frank & Gilovich, 1988; Webster et al., 2012). Past studies demonstrated that traffic participants chose larger gaps when the approaching vehicle appeared to be more threatening, although these studies investigated the effect of car size, not brightness (Horswill et al., 2005; Mathieu et al., 2017; Petzoldt et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pictorial distance cues in the experimental environment, such as occlusion, relative size, relative density, and height in visual field, will support pedestrians' TTC judgments (DeLucia, 2004;DeLucia et al, 2003;Vincent & Regan, 1997). The vehicle size may affect pedestrians' crossing choices: Larger vehicles, such as vans, have been shown to lead to relatively lower TTC estimations when compared with smaller vehicles, such as compact cars (Caird & Hancock, 1994;DeLucia et al, 2003;Horswill et al, 2005;Mathieu et al, 2017;Petzoldt et al, 2017). A within-subject design and the use of similarsize vehicles substantially reduce the impact of any of these confounding factors on the question investigated in our experiment.…”
Section: Related Workmentioning
confidence: 99%
“…Referencing several sources that have found motorists to be consistently more conservative when confronted with larger vehicles, it was suggested that factors other than perceived speed or time-to-collision TTA play an important role for the differences in gap acceptance between different types of vehicles such as expected cost/consequence of an accident. In a following controlled video experiment, Petzoldt et al (2017) found that vehicle size and perceived threat correlated substantially. However, it was unclear to what degree these factors contributed to pedestrian’s crossing decisions or perceived TTA.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, one of the implicit cues reflects communication via relative position (chronemics): an HGV driver choosing to stop further from the stop line when a cyclist is present in order to ensure a sufficient safety margin to the cyclist ( Pokorny and Pitera, 2019 ; Kircher and Ahlström, 2020 ). Three other implicit cues that we identified reflect communication via movements and proximity (kinesics and proxemics): pedestrians accepting a gap and deciding to cross the street ( Petzoldt et al, 2017 ), an HGV driver considerably reducing the speed when encountering a VRU to signal his/her willingness to give way ( Schindler and Bianchi Piccinini, 2021 ), and cyclists dismounting their cycles to get priority at a zebra crossing ( Pokorny and Pitera, 2019 ). The rest of the implicit cues reflect a combination of eye/body language (oculesics/kinesics) (an HGV driver or cyclist directs his/her head and glances towards the interacting partner to get perception of the situation and possibly to signal a request for movement or perception, Kircher and Ahlström (2020) , Kircher et al (2020) , Richter and Sachs (2017) , and Schindler and Bianchi Piccinini (2021) ), and a combination of kinesics, proxemics and chronemics [an HGV approaching a cyclist and choosing to remain behind in order to leave the opportunity for the cyclists to cross first, Kircher and Ahlström (2020) ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation